The occurrence of gonadal dysgenesis in association with monozygotic twinning. - Karp, L (1975)
A case is presented of a monozygotic twin pair, discordant for phenotypic sex, in which the female member showed gonadal dysgenesis and chromosomal mosaicism. Review of the pertinent literature reveals that in monozygotic twin pairs, phenotypic and karyotypic concordance is the usual occurrence for Down's and Klinefelter's syndromes, whereas discordance often accompanies gonadal dysgenesis. Mosaicism is a frequent concomitant of gonadal dysgenesis in monozygotic twins. Our case strengthens the probability of a real association between mosaicism and monozygotic twinning in gonadal dysgenesis.